1993
DOI: 10.1111/j.2042-3306.1993.tb02998.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial occurrence of narcolepsy in Miniature Horses

Abstract: Summary In an investigation of 2 closely related Miniature Horses with a history of excessive sleepiness, depression and episodes of collapse, a diagnosis of narcolepsy was made on the basis of neurological examination and pharmacological testing. Further investigations included electroencephalographic examination (KEG), and analysis of protein content, cell count and monoamine metabolite concentrations of lumbosacral cerebrospinal fluid (CSF). There were no abnormalities noted in the EKGs, and no consistent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…The regression of clinical signs as seen in two of our cases also was observed over an 8-month period by Lunn et al (1993) in Miniature horses. In comparison, Sweeney et al (1983) observed one case of narcolepsy over 39 months with no progress noted and in this case clinical signs of narcolepsy did not change during this time period.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The regression of clinical signs as seen in two of our cases also was observed over an 8-month period by Lunn et al (1993) in Miniature horses. In comparison, Sweeney et al (1983) observed one case of narcolepsy over 39 months with no progress noted and in this case clinical signs of narcolepsy did not change during this time period.…”
Section: Discussionsupporting
confidence: 82%
“…In the papers by Lunn et al (1993) and Sweeney et al (1983), physostigmine increased uncoordination and weakness but did not cause complete collapse in the affected horses. The only complete collapse in narcoleptic horses was described by Sheather (1924) in Suffolk foals and by Lunn et al (1993) in Miniature horses. The forms of cataplexy may vary among animal species.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations